2018
DOI: 10.1111/psyg.12329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms in elderly cancer patients receiving chemotherapy and influencing factors

Abstract: The prevalence of depressive symptoms in elderly cancer patients receiving chemotherapy was similar to that in the geriatric population without cancer. It was also consistent with previous studies on elderly cancer population. Pain was found to be a factor related to depressive symptoms. The prevalence of depression may be reduced by pain control. The treatment of depression may both improve the patient's quality of life and enhance their compliance with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
2
15
1
1
Order By: Relevance
“…Even though the chemotherapy duration has shown no significant association with depression in few pieces of literature [30,31]. The odds of depression among cancer patients who…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the chemotherapy duration has shown no significant association with depression in few pieces of literature [30,31]. The odds of depression among cancer patients who…”
Section: Discussionmentioning
confidence: 99%
“…Even though the chemotherapy duration has shown no significant association with depression in few pieces of literature [ 30 , 31 ]. The odds of depression among cancer patients who took chemotherapy for more than six months was higher than their counterparts in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, older adults (≥70 years) account for 50% of all new cancer diagnoses, about 70% of cancer deaths, and the number of older patients with cancer is growing due to the aging population (Atag et al, 2018;Bluethmann et al, 2016;Cancer Registry of Norway, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health for older patients with cancer is understudied, despite its impact on cancer-related outcomes (Anguiano et al, 2012;Mitchell, 2018;Parpa et al, 2015;. Depression is the most common mental health condition in older patients with cancer, and the reported prevalence varies from 13 to 45% between studies (Atag et al, 2018;Duc et al, 2017;Saracino et al, 2017;Weiss Wiesel et al, 2015). Whereas some longitudinal studies of older patients with cancer have shown an association between depression and increased mortality (Gouraud et al, 2019;Lloyd-Williams et al, 2009), others have not (Ferrat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation